Regulatory immune cells in transplantation. - Wood, K; Bushell, A; Hester, J (2012)
Immune regulation is fundamental to any immune response to ensure that it is appropriate for the perceived threat to the host. Following cell and organ transplantation, it is essential to control both the innate immune response triggered by the injured tissue and the adaptive immune response stimulated by mismatched donor and recipient histocompatibility antigens to enable the transplant to survive and function. Here, we discuss the leukocyte populations that can promote immune tolerance after cell or solid-organ transplantation. Such populations include regulatory T cells, B cells and macrophages, as well as myeloid-derived suppressor cells, dendritic cells and mesenchymal stromal cells. We consider the potential of these regulatory immune cells to develop and function in transplant recipients and their potential use as cellular therapies to promote long-term graft function.